Adventures in time, gender and therapeutic practice. Embracing a queer systemic way of working with gender expansive families - Middleton, Amanda (Murmurations: Journal of Transformative Systemic Practice, 2022)
This paper is an adaption of a keynote address delivered at the Association of Family Therapy Conference 2022. Gender attracts our attention. The reference points for this living and lived concept are changing as people inhabit new truths and reclaim ancient wisdoms of gender. Therapists face the challenge of holding multiple and heart-felt truths about what gender can be in the context of increasingly polarised views of what gender should be. In this paper, I examine how binary gender, created by pathologising colonial practices restricts the psychotherapeutic imagination of what gender and sexuality can be. I encourage practitioners to leave what Hare-Mustin calls the mirrored room (1994) in which dominant socio-political discourses limit possibilities. I discuss how installing a mirror ball, a symbol of queer joy and celebration, in practice spaces would create a fracturing and queering of discourses reflecting wider lived experiences, communities and language practices.